2020
DOI: 10.1177/0954411920978052
|View full text |Cite
|
Sign up to set email alerts
|

An effective heterogeneous whole-heart mathematical model of cardiac induction system with heart rate variability

Abstract: The main objective of this research work is to develop an effective mathematical model of cardiac conduction system using a heterogeneous whole-heart model. The model is in the form of a system of modified Van der Pol and FitzHugh-Nagumo differential equations capable of describing the heart dynamics. The proposed model extends the range of normal and pathological electrocardiogram (ECG) waveforms that can be generated by the model. The effects of the respiratory sinus arrhythmia (RSA) and the Mayer waves (MW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…A modified model is presented in this section. It depends mainly on the work developed in [5] and utilized in [6,7]. The heart is represented by two main components, the cardiac conduction system, and the atrial and ventricular muscles.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A modified model is presented in this section. It depends mainly on the work developed in [5] and utilized in [6,7]. The heart is represented by two main components, the cardiac conduction system, and the atrial and ventricular muscles.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Each process is represented by an AP model. The motivation of utilizing the AP model instead of the of the Fitz-Hugh-Nagumo (FHN) model used in [5][6][7] is that the action potential produced by the AP model has greater resemblance to the myocardial action potential with no super-repolarized state which could be developed in FHN model. Also, the additional parameter 𝜸 𝟎 termed as refractoriness controls the action potential duration (APD) [2,8] which is very important in modeling BBB.…”
Section: Aliev-panfilov Model For Cardiac Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical models have been developed to describe some biological processes, for example cardiac induction system [18], hepatitis C virus [19,20], muscle activation dynamics [21], neurons models [22] and analysis for tumor-immune interaction [23]. A review of tumor immunological models can be found in [24].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been made in the last decade to produce digital twins for clinical applications and cardiac modelling has been among the fastest growing fields. Leaving aside the wealth of literature dealing with individual parts of the heart, recent examples include the computational investigation of electromechanical features [1][2][3] , the influence of cardiac contraction on the electrocardiogram (ECG) 4 and of the heart rate variability 5 ; recent review papers 6,7 give a detailed account of whole-heart electromechanical models.…”
Section: Introductionmentioning
confidence: 99%